Insight into the Diels-Alder reaction: A green chemistry revisitation of the synthesis of a cantharidine-like trypanocidal pilot-molecule - Gbaguidi, A. Fernand; Kasséhin, Urbain C.; Prevost, Julien R. C.; Frederick, Raphaël; McCurdy, Christopher R.; Poupaert, Jacques H. (My University, 2015)
Relying on a straightforward « Green-Chemistry » based approach, this article reports an optimized Diels-Alder (DA) experimental set-up allowing for this reaction to be cleanly operated in the presence of water used both as solvent and catalyst. This work was initiated to synthesize a cantharidine-derived trypanocidal pilot-molecule. Diels-Alder cyclo-addition between anthracene-9-methanol and maleimide in water was selected as benchmark reaction and demonstrated how water as a solvent can be used not only because of its more benign impact on the environment but also because it improves some key aspects (rate, yield, ease of isolation) of the reaction. Adjunction of lithium chloride into the reaction medium adds a significant incremental benefit to the overall yield due to its oxophilic character increasing electron demand at dienophile’s double bond. Our set-up illustrates a typical condition of « on-water » reaction rather then « in-water » reaction conditions. Conclusively, in the DA reaction of our benchmark reaction, water not only behaves as a green solvent but also as a powerful catalyst.
Keywords: Diels-Alder reaction; Green chemistry; Cantharidine; antitrypanocidal agents